Lepidópteros e inimigos naturais de Myrica faya da Ilha de São Jorge. - Vieira, Virgílio; Silva, Luís; Dupont, Sonia; Martins, Rosa; Pombo, Dalberto (Universidade dos Açores, 1993)
VII Expedição Científica do Departamento de Biologia - São Jorge e Topo - 1992. A list of butterflies and moths collected during the "São Jorge e Topo 92 Scientific Expedition", in June/July 1992, at São Jorge island (Azores) is presented. As a result of this survey, 26 confirmed species were found, of which FIVE are for the first time reported for São Jorge island. Some remarks are also given about Mythimna unipuncta (Haw.) (Lep., Noctuidae) and the relationship between armyworm and its natural enemies, specially Apanteles militaris Walsh (Hym., Braconidae). Observations of Lepidoptera and other insects associated with Myrica faya Aiton (Myricaceae) are reported.